Screening of Three Echinoderm Species as New Opportunity for Drug Discovery: Their Bioactivities and Antimicrobial Properties. (1st March 2018) - Stabili, Loredana; Acquaviva, Maria Immacolata; Cavallo, Rosa Anna; Gerardi, Carmela; Narracci, Marcella; Pagliara, Patrizia
Abstract : Echinoderms are a renewable resource with an economic value due to their increasing demand as food and/or source of bioactive molecules exerting antitumor, antiviral, anticoagulant, antioxidant, and antimicrobial activities. In this framework, the present study is aimed at investigating the antibacterial, antioxidant, and hemolytic activities in the three Echinoderm species Echinaster sepositus, Arbacia lixula, and Sphaerechinus granularis . The sea star E. sepositus showed lysozyme-like activity (mean diameter of lysis of 13.4 ± 0.2 mm), an antimicrobial activity against the human emerging pathogens Staphylococcus aureus, Pseudomonas aeruginosa, and Candida famata, and a strong lytic activity (100 ± 0.05 %) towards the human red blood cells. Furthermore A. lixula and E. sepositus had the highest antioxidant activity (1792.75 ± 233.7 and 1765.65 ± 484.58 nmolTE/mL, resp.). From toxicological assays, it was shown that E. sepositus was not toxic towards HeLa cells and Vibrio fischeri, encouraging the exploitation of this species in the pharmaceutical field. Therefore, our findings have implications due to the ongoing explosion of antibiotic-resistant infections because of the new opportunistic pathogens and the need to discover antibacterial agents with new modes of action. Also the recorded antioxidant activity taking into account the need to find natural antioxidants useful for human health is intriguing.